Founding of the Big Data Statistics Branch. Issue 1 (2nd January 2019) - Wang, Shanping
ABSTRACT: The founding conference of the Big Data Statistics Branch (BDSB) of the Chinese Association for Applied Statistics (CAAS) was held on 8 December 2018, at East China Normal University (ECNU), Shanghai, China. More than 600 experts and scholars attended the conference. Professor Zhang Riquan was elected as the chairman of the first Board of Directors of the BDSB. Fang Xiangzhong, Chairman of the CAAS, delivered a speech. Professor Wang Zhaojun and Dr Liu Zhong delivered, respectively, keynote reports on the development of Big Data researches and practices, at the conference. The BDSB will be dedicated to building a high-level big data statistics exchange platform for experts and scholars in universities, governments, enterprises, and other fields to better serve the society and serve the country's major strategies.